Planning a Green Belt Round an Industrial Complex in Uttar Pradesh - Mathur, R. S.; Gogate, M. G. (Indian Forester, 1983)
Based on Bombay High naptha available from Mathura refinery, the Govt. of India is setting up a Petro-chemical complex at Salempur on Mathura-Barellly Highway, District Aligarh, U.P. Unless timely action is taken during the design of construction and operation to contain the same, such complexes have the possibi1ity of thermal and chemical pollution of environment. The project planning authorities mooted the idea of creating a green belt around the proposed complex to be developed by the U. P. Forest Department in consultalion with F. R. I. Trees play an important role in the maintenance and amelioration of environment; they not only improve the atmosphere through absorption of carbon-dioxide and other obnoxious gases and release oxygen, but also help in trapping dust particles and etfuluents in water discharges. Evapo-transpirational processes also moderate temperature to some extent. While doing so, trees also provide aesthetic beauty. In view of the above, it was decided to conduct an indepth study on extent and quality of green belt and the manner in which the same could be achieved most elfeelively. Keeping in view the constraints imposed by locality factors, such as alkaline soil, water logging etc. as also the impact of proposed petrochemical complex, a strategy for establishing of green belt is being evolved. This paper describes the considerations of the choice of species, planting techniques and manner in which the green belt need be maintained. Such an approach will ensure development with the least ecological disturbance i.e. development with out destruction and will provide much needed data base for integrating tree planting while planning major industrial complexes.